2019
DOI: 10.1016/j.jid.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A Monoallelic Two-Hit Mechanism in PLCD1 Explains the Genetic Pathogenesis of Hereditary Trichilemmal Cyst Formation

Abstract: Trichilemmal cysts are common hair follicleederived intradermal cysts. The trait shows an autosomal dominant mode of transmission with incomplete penetrance. Here, we describe the pathogenetic mechanism for the development of hereditary trichilemmal cysts. By whole-exome sequencing of DNA from the blood samples of 5 affected individuals and subsequent Sanger sequencing of a family cohort including 35 affected individuals, this study identified a combination of the Phospholipase C Delta 1 germline variants c.90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…A monoallelic "two-hit" mechanism leads to trichilemmal cyst formation To date, dominant truncating and recessive missense germline variants in PLCD1 have been identified in patients with familial leukonychia (Kiuru et al, 2011). In this study by Hörer et al (2019), a dominantly inherited haplotype with a synonymous and missense variant seen in tandem constitutes a "high-risk allele", and this genetic difference may account for the lack of leukonychia in these patients. This allele predisposes to the acquisition of in cis somatic variants within the C2 domain of PLCd1, which is associated with cyst formation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A monoallelic "two-hit" mechanism leads to trichilemmal cyst formation To date, dominant truncating and recessive missense germline variants in PLCD1 have been identified in patients with familial leukonychia (Kiuru et al, 2011). In this study by Hörer et al (2019), a dominantly inherited haplotype with a synonymous and missense variant seen in tandem constitutes a "high-risk allele", and this genetic difference may account for the lack of leukonychia in these patients. This allele predisposes to the acquisition of in cis somatic variants within the C2 domain of PLCd1, which is associated with cyst formation.…”
Section: Discussionmentioning
confidence: 87%
“…This work by Hörer et al (2019) is important as it highlights PLCd1 as an important protein in the maintenance of human hair follicle homeostasis. In addition, the PLCD1 "high-risk" allele identified may inform the interpretation of genetic tests in families with trichilemmal cysts.…”
Section: Discussionmentioning
confidence: 96%
“…Since we have not performed functional studies, we can only speculate on the mechanism that the genetic changes result in the trichilemmal cyst phenotype. However, Horer and coworkers 19 have shown that the somatic and germline mutations cause additive loss in PLCD1 enzyme activity. Thus, somatic and germline mutations in the same allele may combine to cause loss of function thereby reducing the amount of active enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the molecular mechanisms responsible for developing these cystic lesions, genetic susceptibility was described for simple TC in some cases: hereditary cases may develop with an autosomal dominant type of transmission, involving incomplete penetrance [1,20,21]. TC development has been recently related with phospholipase C delta 1 (PLCD1), probably via an inherited PLCD1 high-risk allele and somatic spontaneous mutation on the other allele [20,21]. Very little mutation analysis has been performed on PTTs: there were described genetic anomalies, mainly aneuploidy, within some PTT [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports had related these genetic alterations with malignant change [22,23], associated occasionally with TP53 deletion [12]. The precise mechanism responsible of the proliferative ability of PTT has been not yet clarified, but the accumulation of mutations on tumour suppressor genes seems a possible option [20].…”
Section: Introductionmentioning
confidence: 99%